THE ROLE OF INTERACTIVE METHODS IN DEVELOPING STUDENTS’ CREATIVE THINKING IN VISUAL ARTS LESSONS - Ataullayeva E’zoza Mansur qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the role of interactive methods in fostering students’ creative thinking during visual arts lessons. Drawing on Shovdirov S.A.’s research, the study highlights the effectiveness of collaborative activities, practical exercises, and creative assignments in enhancing students’ artistic skills, independent thinking, and problem-solving abilities. The article also examines the pedagogical and psychological foundations of using interactive approaches to improve engagement and motivation in visual arts education.